In vitro antifungal activity of luliconazole against nondermatophytic moulds. (23rd November 2019) - Maeda, Jun; Koga, Hiroyasu; Yuasa, Kou; Neki, Daisuke; Nanjoh, Yasuko; Inagaki, Katsuhiro; Reangchainam, Sutthirat; Kampirapap, Kowit; Makimura, Koichi; Harada, Kazutoshi; Tsuboi, Ryoji
Abstract: In vitro antifungal activity of luliconazole against nondermatophytic moulds causing superficial infections was compared with that of five classes of 12 topical and systemic drugs. The minimum inhibitory concentration (MIC) of the drugs against the genera of Neoscytalidium, Fusarium, Aspergillus, Scedosporium, and Alternaria was measured via modified microdilution method. In results, the nondermatophytic moulds were found to be less susceptible to drugs to which Neoscytalidium spp. and Fusarium spp. were typically drug resistant. However, luliconazole was effective against all the genera tested, including afore-mentioned two species, and had the lowest MICs among the drugs tested.